FAKTOR – FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT: STUDI PADA AUDITOR INSPEKTORAT PROVINSI BENGKULU - Sevtiandary, Ranny (JURNAL FAIRNESS, 2019)
The purpose of this study is (1) to analyze the influence the effect of independence on audit quality, (2) to analyze the influence the effect motivation on audit quality, (3) to analyze the influence the effect commitment on audit quality, (4) to analyze the influence the effect experience on audit quality and (5) to analyze the influence the effect competence on audit quality. The data used is the primary data obtained from the questionnaire distributed to the auditor of the Provincial of Bengkulu. The method used is a multiple linear analysis. The results of this study indicate that independence and competence affect audit quality. However, commitmen, motivation, and experience have no effect to audit quality.